Effectiveness and time-course adaptation of resistance training vs. plyometric training in prepubertal soccer players - Negra, Y.; Chaabene, H.; Stögg, T.; Hammami, M.; Souhaiel Chelly, M.; Hachana, Y. (Journal of Sport and Health Science, 2020)
This study aimed to assess the effectiveness and time course for improvements in explosive actions through resistance training (RT) vs. plyometric training (PT) in prepubertal soccer players. Methods: Thirty-four male subjects were assigned to: a control group (n = 11); an RT group (5 regular soccer training sessions per week, n = 12); a PT group (3 soccer training sessions and 2 RT sessions per week, n = 11). The outcome measures included tests for the assessment of muscle strength (e.g., 1 repetition maximum half-squat test), jump ability (e.g., countermovement jump, squat jump, standing long jump, and multiple 5 bounds test), linear speed (e.g., 20 m sprint test), and change of direction (e.g., Illinois change of direction test). Results: The RTG showed an improvement in the half-squat (delta = 13.2%; d = 1.3, p < 0.001) and countermovement jump (delta = 9.4%; d = 2.4, p < 0.001) at Week 4, whereas improvements in the 20-m sprint (delta = 4.2%; d = 1.1, p < 0.01); change of direction (CoD) (delta = 3.8%; d = 2.1, p < 0.01); multiple 5 bounds (delta = 5.1%; d = 1.5, p < 0.05); standing long jump (delta = 7.2%; d = 1.2, p < 0.01); squat jump (delta = 19.6%; d = 1.5, p < 0.01); were evident at Week 8. The PTG showed improvements in CoD (delta = 2.1%; d = 1.3, p < 0.05); standing long jump (delta = 9.3%; d = 1.1, p < 0.01); countermovement jump (delta = 16.1%; d = 1.2, p < 0.01); and squat jump (delta = 16.7%; d = 1.4, p < 0.01); at Week 8 whereas improvements in the 20-m sprint (delta = 4.1%; d = 1.3, p < 0.01); and multiple 5 bounds (delta = 7.4%; d = 2.4, p < 0.001); were evident only after Week. The RT and PT groups showed improvements in all sprint, CoD, and jump tests (p < 0.05) and in half-squat performance, for which improvement was only shown within the RTG (p < 0.001). Conclusion: RT and PT conducted in combination with regular soccer training are safe and feasible interventions for prepubertal soccer players. In addition, these interventions were shown to be effective training tools to improve explosive actions with different time courses of improvements, which manifested earlier in the RTG than in the PTG. These outcomes may help coaches and fitness trainers set out clear and concise goals of training according to the specific time course of improvement difference between RT and PT on proxies of athletic performance of prepubertal soccer players.